Dietas da moda realizadas por praticantes de atividade física - Franco, Ellen Serrão (Brasil, 2024)
Currently, there is a high demand among physical activity practitioners for fad diets with the aim of promoting weight loss or gaining lean mass quickly. These diets are followed through research on popular internet sites, in addition to social networks and recommendations from friends and professionals not qualified to prescribe diet therapy, seeking the “perfect body” quickly. The aim of this paper was to carry out a survey on the use of diets by those who practice physical activities in gyms in the city of Coari (AM). A descriptive experimental study was carried out with the aim of investigating the use of fad diets by practitioners of physical activity, through the application of a self-completed questionnaire. A total of 100 individuals participated in this study, with the majority of individuals aged between 21 and 30 years old and practicing bodybuilding for 4 to 6 days and training daily for 1 to 2 hours. Regarding the diets most followed by individuals, low carb and high protein diets stand out. Participants were also asked whether they felt certain symptoms frequently and, among the symptoms reported, weakness (11%), tiredness (15%) and headache (12%) were highlighted. One of the worrying points is that the majority of participants did not have a nutritionist's recommendation to follow the diet, which may have influenced the adverse symptoms described. With the results obtained in the study, we concluded a high prevalence of adherence to fad diets by gym users in the municipality of Coari.